Cyproterone acetate vs leuprolide acetate in combination with transdermal oestradiol in transwomen: a comparison of safety and effectiveness. (21st March 2016) - Gava, Giulia; Cerpolini, Silvia; Martelli, Valentina; Battista, Giuseppe; Seracchioli, Renato; Meriggiola, Maria Cristina
Summary: Objective: To retrospectively compare the effectiveness and safety of 1‐year administration of transdermal oestradiol (TE) with cyproterone acetate (CPA) or leuprolide acetate (Leu) in transwomen. Design, patients and measurements: Forty transwomen received 50 mg of CPA daily orally ( n = 20; CPA+E group) or Leu at a dose of 3·75 mg i.m. monthly ( n = 20; Leu+E group) in combination with TE at a dose of 1 or 2 mg daily for 1 year. Reproductive hormones, biochemical parameters, body composition and bone mineral density were assessed. Results: LH, FSH and total testosterone levels were significantly decreased by month three of hormone administration in both groups and continued to decrease until month 12; the decrease in LH levels in the first 12 months was significantly faster in the Leu+E group. Prolactin was significantly increased at month 12 in the CPA+E group only. Bone metabolism parameters and bone mineral density as detected at DEXA did not significantly change in either group, apart from a statistically significant increase in parathyroid hormone after 52 weeks of Leu administration. Total cholesterol and HDL‐cholesterol were significantly increased in the Leu+E group and reduced in the CPA+E group. No major adverse effects were registered in either group. Psychological well‐being parameters did not differ between the two groups. Conclusions: Preliminary results from this retrospective observational pilot study suggest that CPA and Leu in combination with TE are equally effective in the suppression of gonadotrophins and testosterone levels over 1 year. Whether the different effects on HDL‐cholesterol may lead to long‐term different cardiovascular safety profiles remains to be defined.